Search for type-III seesaw heavy leptons in pp collisions at s √=8 TeV with the ATLAS detector - Alconada Verzini, María Josefina (2015)
A search for the pair production of heavy leptons (N0,L±) predicted by the type-III seesaw theory formulated to explain the origin of small neutrino masses is presented. The decay channels N0→W±l (=e,μ,τ) and L±→W±ν (ν=νe,νμ,ντ) are considered. The analysis is performed using the final state that contains two leptons (electrons or muons), two jets from a hadronically decaying W boson and large missing transverse momentum. The data used in the measurement correspond to an integrated luminosity of 20.3 fb-1 of pp collisions at s=8 TeV collected by the ATLAS detector at the LHC. No evidence of heavy lepton pair production is observed. Heavy leptons with masses below 325-540 GeV are excluded at the 95% confidence level, depending on the theoretical scenario considered.